T&T Clark handbook of public theology - Hübenthal, Christoph 1961-; Alpers, Christiane 1987- (T&T Clark, 2022)
The public sphere / Maureen Junker-Kenny -- Liberal democracy / Hans-Martien ten Napel -- The secular / Christoph Hübenthal -- Post-secularity and the pluralization of public theology / William Barbieri -- The distinction of public theology from political and liberation theologies / Gaspar Martinez -- Public theology as apologetics / Elaine Graham -- The legacy of theological liberalism : a ghost in public theology / Ulrich Schmiedel -- Public theology in the Catholic tradition / Katie Dunne -- A public orthodox theology / Aristotle Papanikolaou -- Post-liberal positions in public theology / Ben Fulford -- Ecumenical collaboration in public theology / Florian Höhne -- Relations to other religions / Manfred Pirner -- Public theology and (social) ethics / Hak Joon Lee -- Public theology and the doctrine of God / Anne Siebesma -- A black soteriological dialogue with public theology / Reggie Nel -- Public theology and ecclesiology / Al Barrett -- Liturgy and public theology / Catherine Pickstock -- Public eschatology : seeking hope in a world of despair / Mary Doak -- Politics / Amy Daughton -- Race, gender, and public theology / Brian Bantum -- Public theology and culture / Graeme Smith -- Economics / Devin Singh -- Ecological theology as public theology / Hilda Koster -- Challenges for public theology : sports / Dries Vanysacker -- Africa / Dion Forster -- Public theology in Asia / Alexander Chow -- Public theology in Australia / Robert Gascoigne -- Public theology in Europe : towards a performative-political approach / Martin Kirschner -- Public theology in North America : commonality amid plurality / Nicholas Hayes-Mota -- Public theology in Latin America / Eneida Jacobsen
Includes bibliographical references and index
Keywords: Öffentliche Theologie; Public theology; Aufsatzsammlung